A Comprehensive Analysis of the Oxygen Inhalation Lounges - Osama Al-Awadhi (University of Science and Technology, Sana'a, Yemen, 2023)
Oxygen lounges have become increasingly popular in recent years as a way to boost energy and alleviate stress. The concept behind oxygen lounges is based on the idea that extra oxygen can provide numerous health benefits, such as increasing energy, improving mental clarity, and reducing stress and anxiety. However, the scientific evidence to support these claims is limited, and there are potential risks associated with their use, such as oxygen toxicity. This article explores the history and science behind oxygen lounges, their potential health benefits, as well as any potential risks associated with their use. Additionally, it discusses the regulation of oxygen lounges in Yemen especially Sana'a that has no establishments of what sort, where there are currently no specific regulations or guidelines for their operation, despite that Sana'a is famous of lacking of oxygen due to the geographical nature of the city, as the city is located on mountain heights. While oxygen lounges may provide some potential health benefits, the scientific evidence on their effectiveness is limited, and customers should approach them with caution, particularly if they have any underlying medical conditions.